Lipid Membranes as Key Targets for the Pharmacological Actions of Ginsenosides - Verstraeten, Sandrine L.; Lorent, Joseph H.; Mingeot-Leclercq, Marie-Paule (Frontiers in Pharmacology, 2020)
In this review, we will focus on the activity of ginsenosides on membranes and their related effects, from physicochemical, biophysical, and pharmacological viewpoints. Ginsenosides are a class of saponins with a large structural diversity and a wide range of pharmacological effects. These effects can at least partly be related to their activity on membranes which results from their amphiphilic character. Some ginsenosides are able to interact with membrane lipids and associate into nanostructures, making them possible adjuvants for vaccines. They are able to modulate membrane biophysical properties such as membrane fluidity, permeability or the formation of lateral domains with some degree of specificity towards certain cell types such as bacteria, fungi or cancer cells. In addition, they have shown antioxidant properties which protect membranes from lipid oxidation. They further displayed some activity on membrane proteins either through direct or indirect interaction. We investigate the structure activity relationship of ginsenosides on membranes and discuss the implications and potential use as anticancer, antibacterial and antifungal agents.